Markers of acute stress in pigs - Breineková, K; Svoboda, M; Smutná, M; Vorlová, L (Physiological research, 2007)
This study explores the biological validation of markers of acute stress in pigs subjected to transportation for slaughter. The stress markers selected for monitoring were neopterin and cortisol. Their levels in pig serum were measured for two porcine stress syndrome genotypes, NN and Nn, after a 30-min transport to a slaughterhouse. Blood samples were withdrawn before transport (control group) and immediately after the animals' arrival (experimental group). The values of neopterin and cortisol measured before the transport were 5.60+/-1.65 nmol/l and 273.54+/-66.17 nmol/l respectively. After the transfer, the concentration of cortisol rose significantly compared to the control (355.69+/-85.13 nmol/l, p<0.01). Neopterin concentrations in the serum (8.25+/-1.60 nmol/l) were also significantly higher (p<0.01) after transportation. The elevated concentrations of both analytes were found to be independent of the genotype. These results document the stimulation of the endocrine system and the immune system that develops in animals undergoing transportation for slaughter.
Keywords: hydrokortison; fyziologický stres; Animals; Stress, Physiological; Transportation; Genotype; Hydrocortisone; zvířata; Neopterin; doprava; genotyp; biologické markery; prasata; Swine; Biomarkers; neopterin